COMPARISON OF NASAL PROFILES IN VARIOUS SKELETAL PATTERNS - Arshad, Tania; Shaikh, Attiya; Fida, Mubassar (Journal of Ayub Medical College Abbottabad, 2013)
Background: The aim of this study was to determine any significant difference in nasal profiles amongst subjects in sagittal and vertical skeletal patterns in a sample Pakistani population, and to determine gender dimorphism if any. Material: The sample was divided into three sagittal and groups, namely skeletal Class I, II, and III, and three vertical groups, namely, normo-divergent, hypo-divergent and hyper-divergent vertical skeletal patterns. On way ANOVA was used to find any difference in nasal profiles amongst vertical and sagittal skeletal patterns, and to assess gender dimorphism, respectively. Results: Statistically significant differences were found between Skeletal Class I, II and III for naso-labial angle, naso-mental angle and soft tissue facial convexity. Furthermore, statistically significant differences were also obtained between males and females for nasal length, nasal depth, columella convexity and nasal bone length. Statistically significant differences were observed for nasal depth 2 and naso-labial angle in the vertical groups. Conclusions: Skeletal Class I, II, and III subjects have different nasal profiles. Nasal profiles are significantly different for males and females; hence it should be taken into consideration while planning ideal treatment for patients. Different vertical patterns are also associated with different nasal forms. It is recommended that further research be done to establish norms in our population for nasal profile. Keywords: Nasal profile, Vertical skeletal pattern, Sagittal skeletal pattern